The First Family detail [compact disc, unabridged] : Secret Service agents reveal the hidden lives of the Presidents - Kessler, Ronald, 1943- (Random House Audio, 2014)
From New York Times bestselling author and award-winning reporter Ronald Kessler, The First Family Detail tells eye-opening, behind-the-scenes stories from Secret Service agents about presidents and their families.